Cell allocation patterns during mammalian pre-implantation development - Sepulveda-Rincon, Lessly P. (2017)
The first cell differentiation in the mammalian embryo occurs during pre implantation development. At blastocyst stage two cell lineages can be distinguished: the inner cell mass (ICM), situated at the embryonic pole and the trophectoderm (TE) at the abembryonic pole. In murine embryos, it has been suggested that the first cleavage plane might be related with the embryonic-abembryonic (Em-Ab) axis at the blastocyst stage. So the daughter cells of the two-cell embryo might be already predisposed to a specific cell lineage further on development. The objective of the present thesis is to investigate the effects of assisted reproductive technologies (ART) factors affecting cell allocation patterns during pre implantation development.